Measurement of regional disparities and economic competitiveness of a regions - Vrtěnová, Lucie; Sobotka, Martin; Malá, Lada (Univerzita Pardubice, 2009)
This article is devoted to the principles of measurement of regional disparities and a regional economic competitiveness and discuss the most frequently used indicators in this measurement. Inasmuch as the regional economic competitiveness is conditional on a large number of sub-factors, it is useful to focus on the ways of measurement of these factors. Their measurement allows to analyze in which competitiveness areas the region has weaknesses and on what the regional development strategy should be focused.
Keywords: regions; Competitiveness; disparities; comparison; indicators of competitiveness